Research on the Impact of Business Environment Optimization in Guangdong Province on Corporate ESG Performance - Liu, Zhengnan; Feng, Jiajun; Huang, Jingqi (International Journal of Global Economics and Management, 2024)
This study examines the relationship between the policy environment in Guangdong Province and corporate ESG (Environmental, Social, and Governance) performance, offering references for government policy-making, suggestions for business strategies aligned with sustainable development trends, and new perspectives for investors to assess corporate social responsibility. Overall, the optimization of the business environment in Guangdong Province has positively influenced corporate governance, enhanced management levels, and laid a solid foundation for long-term corporate development. In the future, companies should continue to adapt to changes in the business environment, improve their governance structures, and achieve sustainable development.